Sustainable disposal behaviour towards fast fashion products among generation z consumers - Tiaw, Alyssa Yuen Qi (2024)
The fast fashion industry is often being criticised for its actions which causes environmental issues due to the increasing consumption of fast fashion products. To minimize the impact, consumers disposal behaviour of fast fashion products plays a critical role. this This research investigates the sustainability disposal behaviour towards fast fashion products, with the focus of Generation Z consumers who been categorised as the largest user of fast fashion products. This research is aims to determine the sustainable disposal behaviour towards fast fashion products among Generation Z consumers. Using quantitative research approach, empirical data were collected through self- administered questionnaires from a convenience sample of 192 Malaysian Gen Z consumers who had prior experience with disposal of fast fashion products. The study found perceived behavioural control, environmental economic factors and consumer perceived ethicality have highly significant effect on the sustainability disposal behaviour towards fast fashion products among Gen Z consumers, while environmental attitudes and social norm do not show significant impact. The study's findings provide valuable insights for fast fashion companies and policymakers in developing sustainable disposal strategies that aligned with Generation Z values, enhancing brand loyalty, and promoting environmental responsibility within the industry